Distance learning as a phenomenon of modern education: teachers' opinion - Tatyana Alexandrovna Ivashchenko; Elena Sergeevna Dvoynikova (Вестник Майкопского государственного технологического университета, 2023)
Today distance learning, is among the most relevant and promising ways of learning which is implemented using the capabilities of modern telecommunication technologies, the main role belongs to the global Internet. Meanwhile, the first experiences of using electronic educational resources in practice took place in the second half of the 20th century in the USA, Great Britain, France, China, determining an important place for distance learning in a number of additional education. The deterioration of the sanitary and epidemiological situation in 2020 sharply actualized the issues of using distance learning technologies, which is a factor confirming the relevance of the research.The purpose of the research is to present the point of view of the pedagogical community on the problem of distance learning in modern conditions.The research objectives are to reveal the category of "distance learning" and a number of related concepts ("online learning", "E-learning", "electronic information educational environment"); to present the experience of the universities of the Republic of Adygea in the use of educational resources (online platforms) in the practice of distance learning of higher and secondary educational institutions; to conduct a survey of the opinion of the pedagogical community on distance learning.Material and the research methods. The solution of the tasks set was facilitated by the use of scientific research methods: theoretical ones (analysis of the experience of using distance learning technologies in the practice of educational institutions, comparison, analogy method); empirical ones (survey, observation, description). The information and analytical base was made up of information resources of the Internet network.The research results. Distance learning is learning remotely using current educational technologies (Internet services, online learning platforms, cloud technologies, etc.). The following educational resources (online platforms) are actively used in the distance learning of the universities of the Republic of Adygea: Zoom, Skype, Moodle. A pilot study of the opinions of teachers (teachers of universities and colleges) has made it possible to identify certain problems of online learning, including the likelihood of a decrease in the quality of training of students in a distance format, a number of technical equipment problems, an insufficient level of digital literacy of teachers, etc.Key conclusions: the basis of distance learning is information and communication resources of the Internet; the optimal software resources for organizing online learning are Zoom, Skype, Moodle; promising is the solution to the problem of creating a unified digital educational platform that allows developing unified information standards for distance learning.